JARWA DHOSOK: WAYS OF CREATING, THEMES, AND FUNCTIONS - I Dewa Putu Wijana (Linguistik Indonesia, 2022)
This paper deals with a Javanese traditional formula widely known as â€œjarwa dhosokâ€. By this formula and motivated by various intentions, Javanese people used to conform wittily the literal meaning of Javanese words with the creative meaning resulted from extension or modification of their consisting syllables. By using a number of data collected from website and added with ones I had found during my 40 year stay in Yogyakarta, I focuse my attention on the approaches of creation, semantic domains, and communicative functions by structural, contextual, and interpretative methods. Mostly â€œjarwa dhosoksâ€ are created by treating the words to be defined as acronyms with final syllabic rhyming pattern, some of them are done with initial and combination of initial and final syllables. Jarwa dhasa created by various kinds of sound changes are much fewer in number. The practises of creating â€œjarwa dhosokâ€ are used to fulfill various kinds of pragmatic function, mainly emotive, connative, poetic, jocular, and metalinguistic function, etc. Even though most of words to be defined inÂ  â€œjarwa dhosoksâ€ are created to be semantically conformed with the intentions, many of them might beÂ  difficult to comprehend by outsiders or unfully pledged speakersÂ  without comprehensive understanding of the Javanese cultural practices in its broadest sense.Â Â Â Â Â Â Â Â